Corruption and illiberal politics in the Trump era
1 online resource
Keywords: "This book explores the nexus of corruption, late capitalism, and illiberal politics in the Trump era. Through deep, contextualized analysis and careful critique it offers valuable perspectives on how corruption is defined and understood in the current historical moment. Is it something new or a continuation of prior patterns of illiberalism? Essays in this collection consider how corruption is practiced, mobilized, or invoked in a range of cases, each of which is embedded within larger concerns about what citizenship, social belonging, honesty, and justice mean in the United States today. The essays examine a constellation of unscrupulous actors and questionable actions, with topics ranging from sex scandals and shady real estate deals to the Trump administration's response to the COVID-19 pandemic. Several essays directly address the increasingly violent rhetoric and the deliberately anti-democratic policies that have flourished during the Trump era. The book draws on anthropological insights and comparative analysis to place Trump's policies and practices in a wider global context. Corruption and Illiberal Politics in the Trump Era will be of great interest to readers from anthropology, sociology, political science and American studies"--